JANTUNG KOTA YANG PERNAH DIAM: PENGALAMAN PKL KOTA BUKITTINGGI PADA COVID-19 - Remaopdea Putri, Hafizah; Oktaviani, Nurul; Januarti, Andini; Ryanto, Syifa; Viska Levindra, Nadia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Heart of A City That Once Stood Still: The Experience of Bukittinggi City Streets Vendors at COVID-19. The Covid-19 pandemic has had a significant impact on people's lives, from economic, social, to psychological aspects. This study aims to explore the experiences of street vendors in Bukittinggi in facing difficult times during the pandemic. This research uses a qualitative approach with phenomenological methods to understand participants' subjective experiences in depth. Data were obtained through semi-structured interviews with two participants who were street vendors and directly affected by the pandemic. The data analysis technique used is Interpretative Phenomenological Analysis (IPA) which aims to understand how individuals interpret their life experiences. The results revealed five main themes and one unique theme, namely social support, negative feelings, gratitude, the impact of the pandemic, and surrender. A unique theme that emerged from one subject was disappointment with relatives.